Popular Fan Culture as an Impeller of Brand Equity: The Case of the South Korean Music Group BTS - Duran , Sherin Karol Benites-; Ramos, Elizabeth Mayuri-; Buiza, Franklin Cordova- (Journal of Ecohumanism, 2024)
The objective of the research was to determine the relationship between the community of followers and brand equity, using as a case study the musical group BTS, ambassadors of South Korean culture. The methodology applied was a quantitative and correlational approach, with data collected through a survey and applied to a sample of 384 participants. The results indicated a high positive relationship between brand community and brand equity, evidenced by a Spearman’s Rho correlation coefficient of 0.713. Moreover, 99.74% of the respondents perceived high or very high brand quality, and 96.88% of them had a high or very high bond with the brand community. This interaction and creation of emotional ties is facilitated by the affinity in tastes and cultural values associated with the brand. It is concluded that as brand value increases, the brand community is strengthened and/or vice versa. The research studies digital participation in fan culture and seeks that the findings can be used by marketers to develop more effective customer acquisition and loyalty strategies.